Stages of behavior change and physical activity barriers in morbid obese subjects. - Elaine Caroline Boscatto; Maria de Fátima da Silva Duarte; Marcius de Almeida Gomes (Universidade Federal de Santa Catarina, 2011)
The objective of this study was to identify the stages of behavior change (SBC) in physical activity and the prevalence of barriers to physical activity in morbid obese subjects before  (retrospective) and after bariatric surgery. An interview was conducted with 30 patients of both gender ranging in age from 23 to 61 years (39.4 ± 10.5 years), who underwent bariatric surgery at the University Hospital of the Federal University of Santa Catarina, Florianópolis. Descriptive statistics and the nonparametric McNemar test were used for data analysis, with the level of significance set at 5%. Most subjects were women (80.0%), married (73.3%), received three minimal wages (53.5%), and had incomplete elementary school (50.0%). The mean body mass index was 46.9 ± 6.39 kg/m2 before surgery and 32.4 ± 6.09 kg/m2 after surgery. Analysis of SBC showed that 40.0% of the subjects were in the contemplation stage, 20.0% in the preparation stage, 23.3% in the action stage, and 16.7% in the maintenance stage, indicating that the subjects had the intention to or already performed some physical activity. With respect to physical activity barriers, there was a significant reduction in all physical barriers and in most behavioral barriers after surgery. Bariatric surgery positively contributed to decrease most physical activity barriers, but few subjects were regularly active. The development of programs that permit and encourage physical activity in this population is necessary in order to contribute to weight maintenance, in addition to other health benefits.